ANALISIS SEMIOTIKA JOHN FIESKE TENTANG MASKULINITAS DALAM FILM MIRACLE IN CELL NO 7 KARYA LEE HWAN KYUNG - rachmawati, yeanie (Universitas Pendidikan Nasional, 2018)
ABSTRACTMovies as entertainment, information and education can influence thecommunity based on the message content implicit in the film. Korean drama